2009
DOI: 10.1159/000210396
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of L/N-Type and L-Type Calcium Channel Blockers on the Renin-Angiotensin-Aldosterone System in SHR/Izm

Abstract: Background: The L/N-type calcium channel blocker (CCB) cilnidipine has been demonstrated to suppress sympathetic nerve activity. In the present study, we investigated the effects of cilnidipine on the renin-angiotensin-aldosterone system (RAAS) in SHR/Izm rats to confirm differences from the effects of L-type CCB. Methods: Male SHR/Izm rats received vehicle, cilnidipine (0.3, 3 mg/kg) or amlodipine (0.3, 3 mg/kg) by gavage for systolic blood pressure (SBP) measurement. For biochemical analyses, the experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 40 publications
4
38
2
Order By: Relevance
“…Cilnidipine caused a significant decrease in renal cortical norepinephrine levels in SHR/Izumo, although treatment with amlodipine did not decrease the tissue level of norepinephrine. 42 These results suggest that the N-type calcium channel-blocking action of cilnidipine suppresses reflex sympathetic hyperactivity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Cilnidipine caused a significant decrease in renal cortical norepinephrine levels in SHR/Izumo, although treatment with amlodipine did not decrease the tissue level of norepinephrine. 42 These results suggest that the N-type calcium channel-blocking action of cilnidipine suppresses reflex sympathetic hyperactivity.…”
Section: Discussionmentioning
confidence: 88%
“…The sympathetic nervous system is closely related to the renin-angiotensin-aldosterone system. In a recent report, Konda et al 42 investigated the different effects of cilnidipine and amlodipine on plasma aldosterone levels in SHR/Izumo, and they showed that the cilnidipine-treated group had significantly lower plasma aldosterone levels. Furthermore, it has been reported that cilnidipine treatment tended to decrease renal tissue angiotensin II levels in Dahl-salt-sensitive rats.…”
Section: Discussionmentioning
confidence: 99%
“…14 N-type calcium channels have been identified in several types of cells, [15][16][17] and these channels have been reported to mediate rapid calcium influx into the synaptic terminal, which triggers synaptic vesicle exocytosis, neurotransmitter release, synaptogenesis, and gene expression. [18][19][20] We have reported that cilnidipine reduced the plasma aldosterone level in spontaneously hypertensive rats 21 and in a canine model of chronic atrioventricular block that is known to show ventricular electrical remodeling; 22 however, the L-type CCB, amlodipine, did not show any suppressive effect on plasma aldosterone levels. These results suggest that N-type calcium channels are important regulators of the plasma aldosterone level.…”
Section: Introductionmentioning
confidence: 92%
“…Previous in vitro electrophysiological studies have demonstrated that angiotensin II decreases IKr, transient outward K+ currents (Ito) and inward rectifier K+ currents (IK1) of the cardiomyocytes [27][28][29] and that aldosterone decreases Ito. [30] Based on the differences in the effects on the neurohumoral factors between cilnidipine and other drugs, it can be speculate that the inhibitory effect of cilnidipine on the renin-angiotensin-aldosterone system by its N-type calcium channel blocking action [31][32][33][34] may have decreased the suppression of the K+ channels. It is well known that angiotensin II and aldosterone have direct proarrhythmic effects which by several BP-independent mechanisms such as an increase in sympathetic activation, increases in extracellular Ca 2+ entry and Ca 2+ release from intracellular stores and modulation of voltage-dependent potassium channels stated above.…”
Section: Discussionmentioning
confidence: 99%